Analisis Ketersediaan Air dan Kapasitas Tampungan Situ Cikande dan Ciherang Kabupaten Serang - Marzan, Arlan; Taufik, Isvan; Wardhana, Mochamad Wary; Sari, Resti Meliana (Universitas Medan Area, 2024)
Water resources are currently one of the needs that are increasing due to the increase in population and the development of the industrial sector. This causes an imbalance in meeting water and raw water needs in the agricultural industry. Situ Ciherang and Cikande is one of the lakes in Serang Regency which functions as a water catchment conservation area useful for utilizing the water around it. Therefore, it is necessary to analyze the availability of discharge and the volume of storage that Situ Ciherang and Cikande can accommodate. This research aims to analyze the mainstay discharge of Situ Ciherang and Cikande and analyze the storage capacity for the Situ Ciherang and Cikande areas. The data needed in this study are monthly rainfall data and topographic measurement results. The analysis used is rainfall analysis using the algebraic average method, and water availability analysis using DR model analysis. F.J. Mock, and in situ storage analysis. The analysis results show that the water availability of Situ Ciherang and Cikande is 4,902 m3/sec in the rainy season and 0.42 m3/sec in the dry season, for the storage capacity of Situ Ciherang and Cikande is 133,143 m3 with an elevation of +43.00.